Disability and passing : blurring the lines of identity - Brune, Jeffrey A., 1972-; Wilson, Daniel J., 1949- (UPCC book collections on Project MUSE. Global Cultural Studies., 2013)
Passing-an act usually associated with disguising race-also relates to disability. Whether a person classified as mentally ill struggles to suppress aberrant behavior to appear "normal" or a person falsely claims a disability to gain some advantage, passing is a pervasive and much discussed phenomenon. Nevertheless, Disability and Passing is the first anthology to examine this issue. The editors and contributors to this volume explore the intersections of disability, race, gender, and sexuality as these various aspects of identity influence each other and make identity fluid. They argue that the line between disability and normality is blurred, discussing disability as an individual identity and as a social category. And they discuss the role of stigma in decisions about whether or not to pass. Focusing on the United States from the nineteenth century to the present, the essays in Disability and Passing speak to the complexity of individual decisions about passing and open the conversation for broader discussion. Contributors include: Dea Boster, Allison Carey, Peta Cox, Kristen Harmon, David Linton, Michael Rembis, and the editors.